กลยุทธ์การสร้างตราอินเทอร์เน็ตสำหรับเว็บไซต์พาณิชย์อิเล็กทรอนิกส์ - กาศลุน กมลวรรณ (Journal of Multidisciplinary in Social Sciences, 2015)
บทคัดย่อ การวิจัยครั้งนี้เป็นการวิจัยเชิงคุณภาพ มีวัตถุประสงค์เพื่อศึกษากลยุทธ์การสร้างตราอินเทอร์เน็ตของเว็บไซต์พาณิชย์อิเล็กทรอนิกส์ ประเภทเว็บไซต์ช็อปปิ้งออนไลน์ โดยการเก็บข้อมูลจากการสัมภาษณ์เชิงลึก (In-depth Interview) กับกลุ่มผู้ให้ข้อมูล 4 กลุ่ม คือ เจ้าของเว็บไซต์ นักสร้างสรรค์เว็บไซต์ (Web master) ที่เกี่ยวข้องกับการสร้างตราอินเทอร์เน็ตของเว็บไซต์พาณิชย์อิเล็กทรอนิกส์ ประเภทเว็บไซต์ช็อปปิ้งออนไลน์ รวมทั้งนักวิชาการและนักวิชาชีพหรือนักการตลาด ซึ่งเป็นผู้เชี่ยวชาญด้านตราสินค้า ผลการวิจัย พบว่า เว็บไซต์พาณิชย์อิเล็กทรอนิกส์ที่เป็นกลุ่มตัวอย่างนั้น มีแนวคิดการสร้างตราอินเทอร์เน็ตเพื่อส่งเสริมด้านพาณิชย์อิเล็กทรอนิกส์ (E-commerce) ในเรื่องของการซื้อ-ขาย การแลกเปลี่ยนสินค้า โดยเน้นการสร้างความน่าเชื่อถือให้กับเว็บไซต์ เพื่อให้ผู้ซื้อมีความเชื่อมั่นในการทำธุรกรรมซื้อ-ขายทางอินเทอร์เน็ต ในขณะเดียวกันเพื่อให้ผู้ใช้บริการสามารถจดจำเว็บไซต์ได้ง่ายและเป็นการสร้างความแตกต่างให้กับเว็บไซต์ การสร้างตราอินเทอร์เน็ตมีหลักการสร้างเหมือนกับการสร้างตราสินค้าทั่วไป ซึ่งมีความสำคัญเป็นอย่างมากเพราะทำให้มีความแตกต่างจากคู่แข่งขัน โดยเริ่มจากการตั้งชื่อตราสินค้า ดังจะเห็นได้ว่า การตั้งชื่อเว็บไซต์พาณิชย์อิเล็กทรอนิกส์นั้น ควรใช้ชื่อที่สั้น สามารถจดจำได้ง่าย เป็นชื่อที่ง่ายต่อการเรียนรู้ ง่ายต่อการออกเสียง การสะกด การพิมพ์ และชื่อควรมีความสอดคล้องกับสินค้า ซึ่งกระบวนการในการตั้งชื่อนั้นต้องใช้หลักวิทยาศาสตร์ และหลักของศิลปะร่วมผสมผสานกัน การสร้างเอกลักษณ์ (Identity) สำหรับการออกแบบเว็บไซต์ควรมีโทนสี ตราสัญลักษณ์ (Logo) และคำขวัญ (Slogan) ในแบบฉบับของตัวเองให้สามารถจดจำได้ง่าย เพื่อช่วยในการระลึกถึงได้และทำให้เกิดกระบวนการทำซ้ำของแบรนด์หรือตราสินค้าในสมองของลูกค้า แต่ทั้งนี้อาจจะแตกต่างกันในเรื่องของกระบวนการสร้างให้เป็นที่รู้จัก เนื่องจากผลิตภัณฑ์กับเว็บไซต์นั้นมีลักษณะไม่เหมือนกัน ซึ่งผลิตภัณฑ์สามารถสัมผัสจับต้องได้ แต่เว็บไซต์เป็นสิ่งที่จับต้องไม่ได้ *ผลงานวิจัยเรื่องนี้ได้รับทุนส่งเสริมการวิจัย สำหรับพนักงานประจำมหาวิทยาลัยหอการค้าไทย คำสำคัญ : กลยุทธ์ ตราอินเทอร์เน็ต เว็บไซต์ พาณิชย์อิเล็กทรอนิกส์ Abstract This research aims to study strategies of the online brand for e-commerce websites, focusing on online shopping particularly. The study collected data from four groups of informants, including website owners, webmasters for online brands for online-shopping websites, and scholars, as well as professional individuals who are experts in branding. The findings demonstrate the following: 1) E-commerce websites from the sample groups mostly stress branding to uphold e-commerce promotions, including product trading and exchanging, primarily to build trust in online transactions as well as the delivery methods. It should be easy to remember and distinguish. 2) Having an online brand or even a product brand in general is very important in the way that it creates differences among competitors. How to create an online brand is inevitably similar to how to create a product brand. The concerns involve naming, identities, and unique logos, which should be easy to remember in order to avoid brand repetition. 3) Naming an e-commerce website or regular website basically use the same methodology as naming a brand, with stress on being concise, having coherence with the product, and making it easy to remember, learn, pronounce, spell, type, etc. This stage requires a good combination of both science and art. 4) Individualism is crucial as well. It is necessary to make a website remarkable, thus great design is required. Website owners should make sure that the color, logo, and slogan of the website is meaningful, easy to remember, and unique. This helps customers remember the brand. Anyway, the ways to make brands well known are different because products are touchable, but websites are not. *The research findings are sponsored through the research support scholarship especially for associates at the University of the Thai Chamber of Commerce. Keywords: brand building strategies, website, e-commerce